Comparison of Nanohole-Type and Nanopillar-Type Patterned Metallic Electrodes Incorporated in Organic Solar Cells - Wenyan Wang; Yanxia Cui; Kin Hung Fung; Ye Zhang; Ting Ji; Yuying Hao (Nanoscale Research Letters, 2017)
Abstract Both the nanohole- and nanopillar-type patterned metallic electrodes (PMEs) have been introduced in organic solar cells (OSCs) for improving device performances experimentally, but there is few work addressing the similarities and differences between them. In this theoretical work, we systematically compare the impact of the nanohole- and nanopillar-type PMEs on the performance of an OSC based on hybridized cavity resonances. By optimizing the geometrical parameters of each PME, we obtained an interesting result that the integrated absorption efficiencies in the active layer with different optimized PMEs are almost the same (both are equal to 82.4%), outperforming that of the planar control by 9.9%. Though the absorption enhancement spectra of the two different optimal devices are similar as well, the mechanisms of light trapping at the corresponding enhancement peaks are distinct from each other. In a comprehensive view, the nanopillar-type PME is suggested to be applied in the present system, since its optimal design has a moderate filling ratio, which is much easier to fabricate than its counterpart. This work could contribute to the development of high-efficiency OSCs.